Pseudoalteromonas flavipulchra as a dual-functional probiotic for aquaculture: enhancing microalgae growth and antagonizing Vibrio pathogens - Wu, Min-nan; Xu, Yi-jun; Shao, Meng-meng; Wang, Zi-yue; Cao, Jia-yi; Xu, Ji-lin (Frontiers in Marine Science, 2024)
Vibrio disease is a prevalent bacterial infection in aquaculture, and using bacteria with antagonistic properties against Vibrio species as probiotics has emerged as a promising method for disease prevention. Additionally, low biomass productivity of microalgae feed remains a significant bottleneck in bivalve aquaculture. Therefore, it is essential to screen for bacteria that both enhance microalgae growth and inhibit Vibrio pathogens. In this work, we screened seven microalgae growth-promoting bacterial for their antibacterial activity against three Vibrio pathogens, i.e., Vibrio vulnificus, Vibrio parahaemolyticus and Vibrio cholerae, and found that Pseudoalteromonas flavipulchra exhibited antagonistic effects against all three tested Vibrio species. The extracellular products (ECP) of P. flavipulchra exhibited stable antibacterial activity, but it was lost after treatment with heat, alkali, or proteinase K. The proteinaceous material isolated from the ECP by precipitation with 90% saturated ammonium sulfate exhibited antibacterial activity in a concentration-dependent manner. According to these findings P. flavipulchra could be a promising dual-functional probiotic for aquaculture.